2006
DOI: 10.1002/acp.1175
|View full text |Cite
|
Sign up to set email alerts
|

Earwitnesses: effects of accent, retention and telephone

Abstract: An experiment was conducted to investigate the effects of accent, telephone and a relatively long retention interval (3 or 8 weeks) on speaker identification. Three-hundred and sixty participants heard the target's voice and were asked to identify the target by means of a line-up consisting of 6 voices. Half of the participants were given a target-present line-up and the other half a target-absent line-up. The results showed that 24% of participants correctly identified the target in the targetpresent conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
47
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 17 publications
11
47
0
Order By: Relevance
“…This was revealed both in the poorer identification of other-accented targets in target-present lineups and the greater mistaken identification of foils in target-absent lineups. Indeed, the pattern of results accords with those of Kerstholt et al (2006) and of Phillipon et al (2007) in revealing a high false alarm rate to foils when they had an unfamiliar accent. It is worth noting that the other-accent effect revealed here was obtained despite an immediate test and despite the use of clear voices and good listening conditions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This was revealed both in the poorer identification of other-accented targets in target-present lineups and the greater mistaken identification of foils in target-absent lineups. Indeed, the pattern of results accords with those of Kerstholt et al (2006) and of Phillipon et al (2007) in revealing a high false alarm rate to foils when they had an unfamiliar accent. It is worth noting that the other-accent effect revealed here was obtained despite an immediate test and despite the use of clear voices and good listening conditions.…”
Section: Discussionsupporting
confidence: 84%
“…An other-accent effect was still demonstrated, with Australian listeners showing a significant impairment when recognising English speakers with an unfamiliar (English) accent than when recognising English speakers with a familiar (Australian) accent. Similarly, Kerstholt, Jansen, van Amelsvoort, and Broeders (2006) examined the impact of a regional accent by using standard and nonstandard Dutch speakers as targets in a voice recognition task. Despite a smaller difference by varying accent at a regional level, results again supported previous demonstrations, showing an impaired performance with unfamiliar accented speakers both when the target was present, and when the target was absent.…”
Section: Voice Recognitionmentioning
confidence: 99%
“…This is in line with the literature (e.g. Kerstholt et al, 2004Kerstholt et al, , 2006vanWallendael et al, 1994). The effect of the unfamiliar language being stronger in the TA condition is consistent with that of Sullivan and Schlichting (2000).…”
Section: Discussionsupporting
confidence: 82%
“…Studies with longer retention intervals have shown mixed results. While some did not find a decrease in performance between a delay of 1 week and 2 weeks (Van Wallendael et al 1994), 1 week and 8 weeks (Kerstholt et al 2006) or 2 and 8 weeks (McGehee 1944), others have found a significant drop in performance between week 2 and week 3 (Clifford & Denot cited in Bull and Clifford 1984) and also that the false alarm rate increases after 7 days (Yarmey and Matthys 1992). In order to achieve a reasonable degree of ecological validity we decided to use a retention interval of 2 weeks.…”
Section: Choice Of Retention Intervalmentioning
confidence: 94%